2001
DOI: 10.1046/j.1440-1614.2001.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

The concept of appropriate professional boundaries in psychiatric practice: a pilot training course

Abstract: The area of interpersonal relatedness in psychiatry, including the issue of sexual attraction and the possibility of sexual misconduct, can be introduced as a training package in a way which is acceptable to trainees and their supervisors in an Australian setting. The impact of the training module on actual registrar behaviour is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Indeed, Neath () promotes the need to generate a holistic staff well‐being strategy that incorporates a range of mechanisms for workforce development, including multidisciplinary clinical discussion and post‐incident reviews and debriefs. In addition, training in, and appropriate time to focus on boundary management (Vamos ) and case formulation (e.g. Davies et al .…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Indeed, Neath () promotes the need to generate a holistic staff well‐being strategy that incorporates a range of mechanisms for workforce development, including multidisciplinary clinical discussion and post‐incident reviews and debriefs. In addition, training in, and appropriate time to focus on boundary management (Vamos ) and case formulation (e.g. Davies et al .…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…One would hope that education and training to foster awareness in this area has had an impact. Research conducted in a medical school/ residency programme in Australia (Vamos, 2001) showed that, with very little intervention, awareness could be greatly increased -and increased awareness can go a long way to protect against future violations. The numbers in the study were perhaps too low to give such a claim any great validity, but the principles behind such intervention can easily be understood.…”
Section: Prevention and Educationmentioning
confidence: 99%
“…Historically, the field of psychiatry has given much consideration to the topic of boundaries. There exist fairly extensive practice guidelines, 3,4 overarching principles, 5 and some published pilot curricula 6,7 to guide education on this topic. Indeed, given the high incidence of sexual boundary violations in psychotherapy practice, education on boundary vigilance and avoidance of the so-called slippery slope 8 should be mandatory in the field of mental health.…”
Section: Introductionmentioning
confidence: 99%